2015
DOI: 10.1007/s00429-015-1161-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cross-network functional connectivity in chronic pain and its association with clinical symptoms

Abstract: Cortical functioning within the default mode network (DMN) and salience network (SN) is altered in chronic pain patients. The mechanisms underlying these alterations are unknown, but a novel unexamined source is cross-network communication. Aberrant functional connectivity (FC) between the DMN and SN, whose activity is normally anticorrelated, reflects disease severity in many brain disorders. Further, stronger FC between the posterior cingulate cortex (PCC) and anterior insula has been reported in chronic pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
152
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 91 publications
14
152
2
Order By: Relevance
“…In addition to the rsFC with DMN, the CCdp was functionally correlated with the SN. This finding was consistent with a previous study showing that the PCC acts as a hub for the DMN‐SN cross‐network (Hemington, Wu, Kucyi, Inman, & Davis, 2015). Therefore, it was suggested that this “hub” is located in the CCdp.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the rsFC with DMN, the CCdp was functionally correlated with the SN. This finding was consistent with a previous study showing that the PCC acts as a hub for the DMN‐SN cross‐network (Hemington, Wu, Kucyi, Inman, & Davis, 2015). Therefore, it was suggested that this “hub” is located in the CCdp.…”
Section: Discussionsupporting
confidence: 93%
“…A different approach is to measure the dynamic brain connectivity, which varies over time, to enable identification of connectivity patterns that vary with reported levels of ongoing pain. This approach has revealed changes in the default mode and salience brain networks in chronic pain states [107][108][109] . However, a potential confounding factor is the possibility that the judgement and reporting of ongoing pain causes a detectable change in brain processing.…”
Section: O N S E N S U S S Tat E M E N Tmentioning
confidence: 99%
“…DMN, ECN, SMN, and SAN are largely influenced by chronic pain experiences [24,117,118] and are highly interactive with the descending pain modulatory system [24]. In healthy individuals, DMN emerges at rest, mainly deactivated towards stimuli or task [117], and has also been reported to involve in the modulation of pain experience [118].…”
Section: Clinical Implications Of Altered Brain Complexity At Rest Inmentioning
confidence: 99%
“…Sensorimotor network (SMN) is involved in the processing of sensory-discriminative dimension of pain. Cross-network functional connectivity in the sensorimotor cortex is associated with measures of physical function and is influenced by chronic pain [117]. Thalamus, in particular, is a key region in ascending pain modulatory system that transmits sensory/nociceptive stimuli to cerebral and has reciprocal connections with cerebral cortex [124].…”
Section: Clinical Implications Of Altered Brain Complexity At Rest Inmentioning
confidence: 99%
See 1 more Smart Citation